Uncovering the Role of RNA-Binding Protein hnRNP K in B-Cell Lymphomas - Gallardo, Miguel (J Natl Cancer Inst, 2019)
BACKGROUND: Heterogeneous nuclear ribonucleoprotein K (hnRNP K) is an RNA-binding protein that is aberrantly expressed in cancers. We and others have previously shown that reduced hnRNP K expression downmodulates tumor-suppressive programs. However, overexpression of hnRNP K is the more commonly observed clinical phenomenon, yet its functional consequences and clinical significance remain unknown. METHODS: Clinical implications of hnRNP K overexpression were examined through immunohistochemistry on samples from patients with diffuse large B-cell lymphoma who did not harbor MYC alterations (n = 75). A novel transgenic mouse model that overexpresses hnRNP K specifically in B cells was generated to directly examine the role of hnRNP K overexpression in mice (three transgenic lines). Molecular consequences of hnRNP K overexpression were determined through proteomics, formaldehyde-RNA-immunoprecipitation sequencing, and biochemical assays. Therapeutic response to BET-bromodomain inhibition in the context of hnRNP K overexpression was evaluated in vitro and in vivo (n = 3 per group). All statistical tests were two-sided. RESULTS: hnRNP K is overexpressed in diffuse large B-cell lymphoma patients without MYC genomic alterations. This overexpression is associated with dismal overall survival and progression-free survival (P < .001). Overexpression of hnRNP K in transgenic mice resulted in the development of lymphomas and reduced survival (P < .001 for all transgenic lines; Line 171[n = 30]: hazard ratio [HR] = 64.23, 95% confidence interval [CI] = 26.1 to 158.0; Line 173 [n = 31]: HR = 25.27, 95% CI = 10.3 to 62.1; Line 177 [n = 25]: HR = 119.5, 95% CI = 42.7 to 334.2, compared with wild-type mice). Clinical samples, mouse models, global screening assays, and biochemical studies revealed that hnRNP K’s oncogenic potential stems from its ability to posttranscriptionally and translationally regulate MYC. Consequently, Hnrnpk overexpression renders cells sensitive to BET-bromodomain-inhibition in both in vitro and transplantation models, which represents a strategy for mitigating hnRNP K-mediated c-Myc activation in patients. CONCLUSION: Our findings indicate that hnRNP K is a bona fide oncogene when overexpressed and represents a novel mechanism for c-Myc activation in the absence of MYC lesions.